Morphometric characterization of the Todos os Santos river basin in Minas Gerais – Brazil (International Journal of Geoscience, Engineering and Technology, 2020)
This study aimed to morphometric characterization of the watershed of the Todos os Santos River (TSR), located in the northeast of Minas Gerais in Brazil. The Todos os Santos River is one of the most important tributaries of the Mucuri River in the Mucuri Valley. Based on the digital elevation model, known as SRTM (Shuttle Radar Topography Mission) the data were processed in open software to obtain the slope, elevations and aspect values, in addition to delineate the watershed and extracting the streams, which presented through maps, tables and graphs. Furthermore, the whole proceed data were reclassified in a new data range (called classes) according to different criteria for each type of data. The TSR basin has an altimetric amplitude of 830m. The biggest elevation area is class 3 (range: 300 to 400m) with 604.78 km², that represents 27.53% of the total area of the watershed. The most predominant slope is undulating relief, corresponding 49.67% (1091 km²) of the TSR watershed total area. About the aspects (slope orientation) there is trend direction to NE-SW but, the distribution of the aspect classes throughout the river basin showing a balance in the distribution of the slope directions. The results also indicated that the headwaters of the TSR have a higher slope variation after this point, the river shows uniformity behavior. The results accomplished may serve as a guide for other works in the TSR watershed and similar regions.
Keywords: Hydrographic basin; Topography; Relief; Todos os Santos river